Pengaruh Kemampuan Teknologi Digital Terhadap Prestasi Siswa SMA di JABODETABEK - Anton Wardaya; Novianto Budi Kurniawan; Tiodora Hadumaon Siagian (Program Studi Manajemen Pendidikan, 2022)
Abstarct : This study aims to determine the influence of digital technology capabilities on the achievement of high school students in Jabodetabek. This study used a quantitative type of research. The population in this study is high school students in Jabodetabek. The sampling technique is carried out with a non-probability sampling technique of incidental sampling type. Furthermore, calculations were carried out using the Slovin Formula so that a sample of 200 students was obtained. The data collection techniques used are questionnaires, documentation and interviews. The research data was further analyzed using simple linear regression analysis with the help of SPSS 16.0. The results of the data analysis obtained that the sig value was 0.00, so reject Ho so that it can be concluded that there is an influence of digital technology capabilities on student achievement. The influence of technological ability on student achievement is 51.80% and the remaining 48.20% is influenced by other variables.